2019
DOI: 10.28974/idojaras.2019.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Online coupled modeling of weather and air quality of Budapest using the WRF-Chem model

Abstract: Abstract⎯ WRF-Chem is a numerical Eulerian non-hydrostatic mesoscale weather prediction model online coupled with the atmospheric chemistry model, developed mainly by the National Center for Atmospheric Research (NCAR) and the National Oceanic and Atmospheric Administration (NOAA). This model system is a frequently used tool for creating high resolution air quality simulations at different spatial and temporal scales for various air pollutants. In this study, the technical backgrounds of the WRF-Chem model app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
2
0
5
Order By: Relevance
“…The selection of a given chemical mechanism defines the number of species and reactions to be considered during the simulation, the reaction rate constants, and the lumping approach for diverse species. Several studies dedicated to intercompare the performance of various chemical mechanisms have found a large sensitivity of the model concerning the chosen mechanism, which could influence the prediction of gaseous and aerosol species concentration, as well as their physical properties (Balzarini et al, 2015;Kovács et al, 2019;Mar et al, 2016;Zhang et al, 2012). These studies highlight the importance of an adequate selection of the chemical mechanism to achieve an accurate representation of the state of air quality in the different modeling exercises that are carried out.…”
Section: Chemical Mechanismsmentioning
confidence: 99%
“…The selection of a given chemical mechanism defines the number of species and reactions to be considered during the simulation, the reaction rate constants, and the lumping approach for diverse species. Several studies dedicated to intercompare the performance of various chemical mechanisms have found a large sensitivity of the model concerning the chosen mechanism, which could influence the prediction of gaseous and aerosol species concentration, as well as their physical properties (Balzarini et al, 2015;Kovács et al, 2019;Mar et al, 2016;Zhang et al, 2012). These studies highlight the importance of an adequate selection of the chemical mechanism to achieve an accurate representation of the state of air quality in the different modeling exercises that are carried out.…”
Section: Chemical Mechanismsmentioning
confidence: 99%
“…A városon belüli légszennyezettségi viszonyok térbeli eloszlását levegőkémiai modellekkel is leírhatjuk (l. pl. Leelőssy et al, 2017;Kovács et al, 2019), de a beépítettségi viszonyok tényleges hatásait, és az egyes útvonalak menti légszennyezettséget elsősorban a mobil mérések képesek visszaadni.…”
Section: Bevezetésunclassified
“…A légszennyezettségi viszonyok térbeli eloszlását városi környezetben általában levegőkémiai modellekkel írják le (l. pl. Leelőssy et al, 2017;Kovács et al, 2019). A modellszimulációk mellett a hordozható légszennyezettség-mérő műszerek használata is egyre népszerűbb, ugyanis ezek segítségével a személyes kitettséget közvetlenül lehet vizsgálni.…”
Section: Mobil Mérésekunclassified